2020
DOI: 10.1101/2020.02.28.970715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-Transcriptional Circadian Regulation in Macrophages Organizes Temporally Distinct Immunometabolic States

Abstract: Our core timekeeping mechanism, the circadian clock, regulates an astonishing amount of cellular physiology and behavior, playing a vital role in organismal fitness. While the mechanics of circadian control over cellular regulation can in part be explained by the transcriptional activation stemming from the positive arm of the clock's transcription-translation negative feedback loop, research has shown that extensive circadian regulation occurs beyond transcriptional activation in fungal species and data sugge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(102 citation statements)
references
References 86 publications
8
94
0
Order By: Relevance
“…The rhythmic transcriptional activation on the promoters of these genes from the positive arm is believed to be the primary mechanism of output. In addition, recent work in several eukaryotic species has also shown that there is a great deal of post-transcriptional regulation, for example rhythmic proteins arising from non-rhythmic transcripts [22,[41][42][43][44][45]. This suggests that the canonical TTFL control of output has several as yet undiscovered levels of regulation.…”
Section: Circadian Output and Conserved Molecular Oscillatorsmentioning
confidence: 99%
“…The rhythmic transcriptional activation on the promoters of these genes from the positive arm is believed to be the primary mechanism of output. In addition, recent work in several eukaryotic species has also shown that there is a great deal of post-transcriptional regulation, for example rhythmic proteins arising from non-rhythmic transcripts [22,[41][42][43][44][45]. This suggests that the canonical TTFL control of output has several as yet undiscovered levels of regulation.…”
Section: Circadian Output and Conserved Molecular Oscillatorsmentioning
confidence: 99%
“…Immune cell function is dependent on a 24-h circadian rhythm that is regulated by the expression of clock genes [ 10 , 11 ]. Key immune cell types, macrophages and monocytes, have a robust intrinsic circadian clock and a high expression of clock genes [ 12 ]. Molecular circadian rhythms are generated by autoregulatory transcription–translation feedback loops [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…the cell cycle. As multi-omics circadian data becomes more prevalent (Collins et al, 2020;Campbell et al, 2020;Hughes et al, 2017), MOSAIC will provide an important role in finding and understanding both oscillatory and non-oscillatory trends in a variety of organisms and processes.…”
Section: Discussionmentioning
confidence: 99%
“…Hurley et al (2018), that rhythmic RNA expression does not necessarily imply rhythmic protein expression and vice versa (Hurley et al, 2018), These data suggest that there may be extensive post-transcriptional regulation in the clock's output and beyond. The exact mechanisms of this regulation are currently unknown, though translation and degradation are predicted to be involved (Hurley et al, 2018;Lück et al, 2014;Collins et al, 2020).…”
Section: Introductionmentioning
confidence: 99%